The Effect of Financial Literacy, Motivation, And Risk Perception on Stock Investment Interest in National University Students - Prasetyo, Agus; Elwisam; Digdowiseiso , Kumba (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
The purpose of this study is to analyze the influence of financial literacy, motivation, and risk perception on stock investment interest in National University students batch 2019-2020. This study was sourced from primary data generated from respondents' answers through the distribution of a questionnaire. Sampling in this study was 105 respondents using the simple random sampling method. The data analysis technique used in this study is the PLS or Partial Least Square approach using the help of the WrapPLS 7.0 application. Based on the results of research that has been conducted, it is known that financial literacy, motivation, and risk perception have a positive and significant influence on investment interest in National University students batch 2019-2020.